Practicing communication ethics : development, discernment, and decision making - Tompkins, Paula S. (New York, NY : Routledge, 2019)
Practicing Communication Ethics: Development, Discernment, and Decision Making, provides a theoretical framework for developing a personal standard of ethics that can be applied in everyday communication situations. This second edition focuses on how the reader's communication matters ethically in co-creating their relationships, family, workgroups and communities. Through an examination of ethical values including truth, justice, freedom, care, integrity, and honor, the reader can determine which values they are ethically committed to upholding. Blending communication theory, ethics as practical philosophy, and moral psychology, the text presents the practice of communication ethics as part of the lifelong process of personal development and fosters the ability in its readers to approach communication decision-making through an ethical lens.
Preface -- Part 1: Developing a Practice of Communication Ethics -- Chapter 1 The Centrality of Ethics in Human Communication -- Chapter 2 Developing a Personal Ethical Standard for Human Communication -- Chapter 3 Ethical Reasoning about Human Communication -- Chapter 4 Six Ethical Values of Human Communication -- Chapter 5 Applying Values and Principles in Ethical Reasoning -- Part 2: Applying Ethical Theories to Human Communication -- Chapter 6 Traditional Approaches to Ethical Theory -- Chapter 7 Contemporary Alternatives to Modernist Ethical Theories -- Part 3: Four Contexts of Ethical Communication Practice -- Chapter 8 Communication Ethics and Digital Communication -- Chapter 9 Communication Ethics and Community -- Chapter 10 Communication Ethics and Intercultural Communication -- Chapter 11 Your Practice of Communication Ethics.
Includes index.
Keywords: MASS MEDIA